Real-world outcomes of Deep Brain Stimulation for dystonia treatment: Protocol for a prospective, multicenter, international registry - Albanese, Alberto; Jain, Roshini; Krauss, Joachim K. (PloS one, 2024)
Deep Brain Stimulation (DBS) is an established therapeutic approach for the treatment of dystonia. However, to date, no large-scale or comprehensive DBS dystonia patient registry has been yet undertaken. Here, we describe the protocol for a world-wide registry of clinical outcomes in dystonia patients implanted with DBS. This protocol describes a multicenter, international clinical outcomes registry consisting of up to 200 prospectively enrolled participants at up to 40 different sites to be implanted with a constant-current, multiple independent current controlled (MICC) DBS device (Vercise DBS Systems, Boston Scientific) for treatment of dystonia. Key inclusion criteria for registry candidates include the following: understanding of study requirements and treatment procedures, a signed written informed consent form prior to participation, and meeting all criteria established in the locally applicable Instructions for Use (IFU) for the implanted DBS system. Key clinical endpoints include (but are not limited to) the evaluation of disease state (Burke-Fahn-Marsden Dystonia Rating Scale [BFMDRS], Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS), quality of life (Short Form Health Survey-36, Short Form Health Survey-10), and treatment satisfaction (Clinical Global Impression of Change [CGI-Clinician; CGI-Subject; CGI-Caregiver]) at 6-months, 12-months, 2-years, and 3-years post-lead placement. Adverse events are documented and reported using structured questionnaires. Treatment of patients with dystonia using DBS has progressed considering recent technological advances. This international dystonia outcomes registry aims to collect and evaluate real-world clinical data derived from patients who have been implanted with a constant-current, MICC-equipped DBS system (with available directional capabilities), per standard of care.